2010
DOI: 10.1177/1088868310367640
|View full text |Cite
|
Sign up to set email alerts
|

When Do People Rely on Affective and Cognitive Feelings in Judgment? A Review

Abstract: Although people have been shown to rely on feelings to make judgments, the conditions that moderate this reliance have not been systematically reviewed and conceptually integrated. This article addresses this gap by jointly reviewing moderators of the reliance on both subtle affective feelings and cognitive feelings of ease-of-retrieval. The review revealed that moderators of the reliance on affective and cognitive feelings are remarkably similar and can be grouped into five major categories: (a) the salience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
235
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 320 publications
(254 citation statements)
references
References 166 publications
(243 reference statements)
14
235
2
3
Order By: Relevance
“…Alter & Oppenheimer, 2009;Greifeneder et al, 2010;Hansen & Wänke, 2013;Herzog & Hertwig, 2013;Schwarz, 2004;Schwikert & Curran, 2014;Unkelbach & Greifeneder, 2013;Wänke & Hansen, 2015). Nonetheless, in all studies on the FH published so far, recognition speed has been taken as a proxy for fluency, so using new proxies would render our findings difficult to compare to those from previous studies.…”
Section: Assessment Of Fluencycontrasting
confidence: 53%
See 1 more Smart Citation
“…Alter & Oppenheimer, 2009;Greifeneder et al, 2010;Hansen & Wänke, 2013;Herzog & Hertwig, 2013;Schwarz, 2004;Schwikert & Curran, 2014;Unkelbach & Greifeneder, 2013;Wänke & Hansen, 2015). Nonetheless, in all studies on the FH published so far, recognition speed has been taken as a proxy for fluency, so using new proxies would render our findings difficult to compare to those from previous studies.…”
Section: Assessment Of Fluencycontrasting
confidence: 53%
“…In other words, if researchers tap the wrong subprocess (or too few), not much can be learned about subjective fluency. Correspondingly, a large body of research has shown that subjectively experienced fluency might differ substantially from objective measures (see Greifeneder, Bless, & Pham, 2010;Hilbig, 2012;Newell & Shanks, 2007;Sanchez & Jaeger, 2015;Scholl, Greifeneder, & Bless, 2014;Unkelbach & Greifeneder, 2013;Whittlesea & Leboe, 2003).…”
Section: Assessment Of Fluencymentioning
confidence: 99%
“…For example, we would predict that subjective experiences of fluency would have more influence on judgments of fame or truth when the target is temporally proximate than when it is temporally distant. Indeed, there is growing evidence that feelings tend to operate in a similar manner regardless of whether they are affective, cognitive, or bodily (Greifeneder et al 2011; see also Hong and Sun 2012).…”
Section: Theoretical Elaborations and Speculationsmentioning
confidence: 99%
“…The current contribution approaches this question by focusing on feelings of ease or difficulty associated with recalling instances from memory, so-called ease-of-retrieval experiences (Schwarz et al 1991). Although this may not seem intuitive at first glance, ease-of-retrieval experiences have been documented as important sources of information in judgment and decision making upon which individuals frequently draw (e.g., Greifeneder et al 2011a;Schwarz et al 2008). Building on previous evidence and on the idea that different types of information are considered particularly relevant by individuals in a promotion versus a prevention focus, we hypothesize that reliance on ease-ofretrieval is more pronounced for individuals characterized by a predominant promotion orientation as compared to individuals with a predominant prevention orientation.…”
Section: Introductionmentioning
confidence: 99%
“…This so called second or third generation research is of particular importance because knowing that an effect can occur does not provide much information about its ecological importance, since an effect observed in a particular investigation may still be unlikely to occur outside psychological laboratories. To address this question, a recent review identified five major categories of moderators which state that reliance on ease-of-retrieval in judgment likely occurs (a) when ease-of-retrieval feelings exceed a certain threshold of salience, (b) when feelings are perceived as representative of the evaluation target, (c) when feelings are perceived as relevant for the judgment, (d) when judgments are evaluatively malleable, and (e) when processing intensity is low (Greifeneder et al 2011a). To the best of our knowledge, however, there is no evidence concerning whether promotion versus prevention triggers differential reliance on ease-of-retrieval and content, despite there being good reason to expect such an impact, as detailed below.…”
Section: Introductionmentioning
confidence: 99%